2020
DOI: 10.1002/jcsm.12539
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐4 administration improves muscle function, adult myogenesis, and lifespan of colon carcinoma‐bearing mice

Abstract: Background Anorexia, body wasting, inflammation, muscle, and adipose tissue loss are hallmarks of cancer cachexia, a syndrome that affects the majority of cancer patients, impairing their ability to endure chemotherapeutic therapies and reducing their lifespan. In the last 10 years, alterations of protein turnover and impairment of adult myogenesis have been proposed as major contributing factors. Methods Muscle stem cells, including satellite cells, mesoangioblasts, and fibroadipogenic progenitors, were isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 37 publications
(105 reference statements)
3
49
0
2
Order By: Relevance
“…Once activated, SCs start to proliferate and either self-renew for maintaining the muscle stem cell pool or differentiate toward myoblasts and fuse with existing myofibers to increase fiber mass and length (Tidball, 2011). During chronic inflammation conditions, SC number can increase due to inflammatory stimuli, such as those in muscular dystrophies, where the number of SCs is eventually exhausted, or during cancer-induced muscle atrophy, where SCs accumulate in the interstitium (He et al, 2013;Costamagna et al, 2020). Despite their specific location, SCs can be identified by different molecular markers such as PAX7, CD56, and CD82 (Illa et al, 1992;Seale et al, 2000;Tedesco et al, 2017;Rotini et al, 2018;Tey et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Once activated, SCs start to proliferate and either self-renew for maintaining the muscle stem cell pool or differentiate toward myoblasts and fuse with existing myofibers to increase fiber mass and length (Tidball, 2011). During chronic inflammation conditions, SC number can increase due to inflammatory stimuli, such as those in muscular dystrophies, where the number of SCs is eventually exhausted, or during cancer-induced muscle atrophy, where SCs accumulate in the interstitium (He et al, 2013;Costamagna et al, 2020). Despite their specific location, SCs can be identified by different molecular markers such as PAX7, CD56, and CD82 (Illa et al, 1992;Seale et al, 2000;Tedesco et al, 2017;Rotini et al, 2018;Tey et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To date, few papers have directly investigated the changes to skeletal muscle monocytes or MΦs with cancer and/or cancer-associated wasting ( Inaba et al, 2018 ; Costamagna et al, 2020 ). Interleukin-4 (IL-4), a potent stimulator of M2-like MΦs, was shown to attenuate skeletal muscle wasting in the C26 mouse model of cachexia associated with reduced satellite cell accumulation and increased skeletal muscle CD206 protein expression ( Costamagna et al, 2020 ). Protein analysis showed no significant differences between control and C26-tumor bearing mice with F4/80, and CD206 (marker of M2-like MΦs) appears lower in C26 mice but did not achieve statistical significance.…”
Section: Immune Cellsmentioning
confidence: 99%
“…Deficits in the capacity for myogenesis, which is needed for successful muscle regeneration, have been reported in skeletal muscle from preclinical cachexia models and cancer patients, and involve an inability of satellite cells to effectively differentiate to complete the regenerative process ( Penna et al, 2010 ; He et al, 2013 ). Due to the importance of the successful myogenic response in muscle regeneration, signaling pathways disrupting satellite cell activity have been actively investigated as potential therapeutic targets for cancer-induced muscle wasting ( Schwarzkopf et al, 2006 ; He et al, 2013 ; Cerquone Perpetuini et al, 2018 ; Costamagna et al, 2020 ; Schmidt et al, 2020 ). To this end, skeletal muscle satellite cell differentiation has been reported to be rescued in colon-26 induced cachexia in mice through the inhibition or ERK signaling ( Penna et al, 2010 ), and more recently IL-4 administration ( Costamagna et al, 2020 ).…”
Section: Skeletal Muscle Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Costamagna, D et al found the IL-4 treatment would improve the performances and prolonged survival of colon carcinoma-bearing (C26) mice. IL-4 could rescue muscle mass by increasing protein synthesis and promote myogenesis (Costamagna et al, 2020). Du H et al investigated that overexpression of ADAMTS1 in macrophages could active satellite cell and promote muscle regeneration by reduces Notch signaling (Du et al, 2017).…”
Section: Anti-inflammatory Cytokinementioning
confidence: 99%